Orthodoxy and Protestantism through the Centuries - Gjorgjevski, Gjoko (George Fox University, 2018)
The aim of this paper is to describe the history and actual relations between the Orthodox East and the Protestant West. This paper will both examine and show the beginning, the continuation and the present situation of the Protestant-Orthodox dialog, communication, influences, convergences and differences, as well as the disputes and attempts to overcome disagreements. It will give an overview of the most important dialogues and scholarly exchanges over the centuries.
Keywords: Orthodox, Protestant, dialogue